Analisis Kemampuan Pemecahan Masalah Melalui Model Realistic Mathematics Education (RME) Di Sekolah Dasar: A Literature Review - Azizah, Putri; Arrahim; Endah Sugiharti, Rini (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
Problem solving ability is an important competency for students to have, in understanding the situations they face every day. Through skills and abilities, students are able to solve mathematical problems using basic knowledge. This research aims to analyze, describe and answer research questions regarding the impact of implementing the Realistic Mathematics Education (RME) model on elementary school students' ability to solve mathematics problems. This research examines the literature using the Systematic Literature Review (SLR) research method. Data collection was obtained by searching for articles that have been published and indexed into the Google Scholar database with a maximum publication period of 6 years (2019-2024) and 10 articles used in this research. Based on a literature study of the research conducted, problem solving abilities are based on several main indicators: understanding the problem, planning how to solve it, resolving the problem, and then evaluating. The results of the research provide recommendations, namely that the use of the Realistic Mathematics Education (RME) model with the help of tangram media can be used as an alternative in helping teachers improve students' mathematical problem solving abilities in elementary schools.